Bilateral retinoblastoma in early infancy - Saiju, R; Duwal, S (Nepalese Journal of Ophthalmology, 2013)
Introduction: Retinoblastoma is the most common primary intraocular malignancy of childhood. It is usually diagnosed before the age of 5 years. In spite of its early onset in most children, retinoblastoma is rarely diagnosed congenitally or even within the first 3 months of life. Objective: To report a case of retinoblastoma in early infancy. Case: This was a case of the earliest presentation of retinoblastoma in a female child 20 days after birth. The presenting complaint was of leucokoria noticed by the mother 13 days after birth. The father of the child was also found to have a suspicious lesion of retinocytoma in one eye and regressed retinoblastoma in the other eye. Conclusion: For early diagnosis of the disease, awareness and knowledge about the modes of presentation of the disease are very important. Similarly, the ophthalmic examination of the parents and siblings with retinoblastoma should always be done to exclude the disease. Nepal J Ophthalmol 2013; 5(9):124-128 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7840